Strategi Komunikasi Penyuluh Agama Hindu dalam Menyampaikan Pesan Ajaran Agama Hindu di Kantor Kementerian Agama Kota Denpasar - Damayanti, Ni Putu Trisna; Yasa, I Ketut Wardana; I Nyoman Surpa Adisastra (UHN IGB Sugriwa Denpasar, 2024)
The expectations of Hindu Religious Counselors in Denpasar City to reach a broader audience through social media do not align with the feedback on the content produced. Although the YouTube account of the Denpasar City Ministry of Religious Affairs has 4,270 followers, the number of likes and comments does not match the number of followers. The research questions in this article are: 1) How is the communication strategy planning of Hindu Religious Counselors in conveying Hindu teachings at the Denpasar City Ministry of Religious Affairs Office? 2) What media are used in the communication strategy of Hindu Religious Counselors in conveying Hindu teachings at the Denpasar City Ministry of Religious Affairs Office? and 3) What is the communication strategy of Hindu Religious Counselors in conveying Hindu teachings at the Denpasar City Ministry of Religious Affairs Office? The theories used include Persuasive Communication, Diffusion of Innovations, and Stimulus-Response. This research is qualitative. Data collection methods include observation, interviews, documentation, literature review, and online references. The research findings are: (1) Hindu Religious Counselors base their planning on the regulations set by the Directorate General of Hindu Community Guidance, specifically Minister of Administrative and Bureaucratic Reform Regulation No. 9 of 2021. (2) Hindu Religious Counselors at the Denpasar City Ministry of Religious Affairs use two types of communication media: offline communication media and online communication media. (3) The messages conveyed by the counselors always follow Tattwa, Susila, and Acara. Keywords: Communication Strategy, Counseling Message, Communication Media